The Effect of Booklet Education on Mothers' Knowledge Related to Stunting - Hany, Alfrina; Vatmasari, Ratih Arum; Putri, Farah Oktaviani; Alizain, Azmy Avi (Universitas Malahayati, 2024)
ABSTRACT The growth and development of children is impacted by stunting, a serious public health issue. Mother knowledge is one aspect that affects stunting. Stunting-related education by booklets could improve mothers' awareness. To analyze the effect of education using booklets on maternal knowledge related to stunting. The study design used was a pre-experiment with a one group pre-test and post-test approach. The sample in this study were mothers who had children aged 0-5 years. The sampling technique used purposive sampling. The instrument used was a stunting knowledge questionnaire. The results of the Wilcoxon-test statistical test showed that there was a significant effect before and after education using booklets on mothers' knowledge related to stunting (p value = 0.002). Therefore, it can be concluded that providing education using booklets is effective in increasing mothers' knowledge related to stunting. Nurses could provide education using educational media such as booklets to increase mothers' knowledge related to stunting. Keywords: Education, Booklet, Stunting, Mothers' Knowledge